STRATEGY FOR OPTIMIZING THE UTILIZATION OF PRODUCTIVE ZAKAT IN THE PERSPECTIVE OF SHARIA ECONOMICS: A CASE STUDY OF BAZNAS BONDOWOSO REGENCY - siti jamila; Moh. Idil Ghufron (Universitas Muhammadiyah Surabaya, 2026)
This study examines strategies for optimizing the utilization of productive zakat in the economic empowerment of mustahik at BAZNAS Bondowoso Regency. The study uses a qualitative case study approach conducted through semi-structured interviews, documentation, and field findings. The informants consisted of BAZNAS administrators, zakat management officers, program companions, administrative staff, and mustahik who received productive business assistance. The data were analyzed using data reduction, data presentation, and conclusion drawing, while data validity was strengthened through source triangulation, technique triangulation, and member checking. The findings show that productive zakat optimization is implemented through five main strategies: administrative and field-based mustahik selection, provision of business tools according to business needs, business mentoring, program monitoring, and strengthening zakat fundraising. Productive zakat contributes to increasing mustahik income, creating independent business opportunities, reducing dependence on informal work, and strengthening local economic activities. However, the program still faces limitations in zakat funds, human resources, and structured monitoring systems. The study contributes to Islamic economic literature by showing that productive zakat can function as a sustainable empowerment instrument when managed through integrated selection, assistance, supervision, and institutional capacity building based on maqasid al-sharia principles.